Determinação multirresíduo de agrotóxicos em berinjela empregando método QuEChERS e UHPLC-MS/MS - Zanchin, Cleusa Fatima (2022)
The intensive use of pesticides in agriculture, especially herbicides, insecticides and fungicides, aims to control pests and diseases in order to increase production. On the other hand, consumers of these products can be exposed to pesticide residues in food, and the maximum residue limits (MRLs) established by legislation must be observed. Therefore, the development of broad and modern analytical methods that allow the monitoring of pesticide residues in food is of great importance. In this work, an analytical procedure based on sample preparation by the QuEChERS method was developed and validated for the multiresidue determination of 111 pesticides in eggplant by ultra-high performance liquid chromatography coupled to serial mass spectrometry (UHPLC-MS/MS). After choosing the best extraction step conditions based on the original QuEChERS method, we evaluated the extract cleaning ability with different sorbents in the dispersive solid phase extraction (d-SPE) step. The sorbent produced from carbon nanotubes stabilized on chitosan sponge (CNT-CS), an efficient and low cost biosorbent, showed the best accuracy results, obtained through recovery tests. The proposed method was validated, showing adequate linearity for all compounds, with determination coefficients greater than 0.990. The UHPLC-MS/MS analyses showed high selectivity, sensitivity and detectability. The quantification limits of the method, considering the levels that presented recovery between 70 and 120%, with RSD ≤ 20%, ranged between 0.005 and 0.025 mg kg-1, below the MRLs established for eggplant, by ANVISA, European Union and Codex Alimentarius. The proposed method was applied to 26 commercial eggplant samples and residues of 27 pesticides were found, nine of them are prohibited in Brazil for this crop. The results showed that the proposed method is efficient and can be used in routine analyses for multiresidue determination of pesticides in eggplant.